Resíduo seco de fecularia na alimentação de frangos de corte suplementados ou não com carboidrases - Broch, Jomara (2015)
The objective of this study was to evaluate the dry residue of cassava (DRC) and its use, associated or not with carbohydrases on production of broiler chickens. In the first experiment 160 Cobb 500 birds from 14 to 24 days old were used, 50% males and 50% females. The treatments were distributed in a completely randomized design in a 2x5 factorial arrangement, with two sexes and five levels of inclusion of DRC (0, 10, 20, 30 and 40%), totaling ten treatments and four replicates, with four birds each. The experimental period lasted ten days, five days of adaptation and five for excreta collection, in which two collections a day were carried out. Subsequently the samples of excreta, feed and DRC were dried in forced circulation of greenhouses air at 55 °C, subjected to analysis of dry matter (DM), crude protein (CP), ether extract (EE), gross energy (GE), neutral detergent fiber (NDF), acid detergent fiber (ADF), calcium, phosphorus, potassium and magnesium. The chemical composition for the DRC was 89.86% DM, 0.98% CP, 3519 kcal kg-1 of EB, 0.19% of EE, 27% NDF, 19.5% ADF, 0.33% calcium, 0.43% phosphorus, 0.46% potassium and 0.12% magnesium, in the natural matter. The mean values of apparent metabolizable energy (AME) AME corrected for nitrogen balance (AMEn) AME coefficient (CAME) and coefficient of AMEn (CAMEn) of DRC in natural matter were 1598 kcal kg-1, 1605 kcal kg-1, 45.42% and 45.61%, according to the methodology proposed by Matterson et al. (1965), respectively. According to another analysis method (ADEOLA, 2000), the AMEn value found may vary from 1789 kcal kg-1 to 1808 kcal kg-1. In the second experiment birds were distributed in a completely randomized design in a 2x5 factorial scheme, consisting of the combination of the addition or not of carbohydrases and five levels of inclusion of DRC, resulting in 10 treatments and with five replicates of 22 birds each. At 21 days of age, two birds each were fasted for 6 hours, for blood brachial puncture. At 42 days old, four birds per pen were slaughtered to determine carcass yield, cut and organs, and percentage of abdominal fat and assessment of meat quality. Between 1-21 days old there was interaction (P<0.05) between supplementation of carbohydrases and DRC for weight gain (WG) and feed intake (FI), which showed decreasing linear effect without the inclusion of carbohydrases. In the period from 1 to 42 days there was interaction (P<0.05) between supplementation of carbohydrases and the inclusion of DRC for WG variables and feed conversion (FC). The inclusion of DRC was responsible for the fall in WG and FI, and worsening FC. With supplementation of carbohydrases, the WG variables FI and FC did not differ (P>0.05) from the control diet (CD). Carcass yields, breast, thigh, drumstick and wing were not influenced (P>0.05) by supplementation of carbohydrases and DRC inclusion levels in phase from 1-21 days. The relative weight of organs was not affected (P>0.05) by inclusion of DRC and addition or not of carbohydrases. The inclusion of carbohydrases provided an increase (P<0.05) in the concentration of cholesterol, triglycerides (TAG), creatinine, gamma GT and blood glucose. The uric acid, aspartate aminotransferase (AST) and total proteins were not affected (P>0.05) by the presence or absence of carbohydrases. The concentration of Gamma GT showed an increase and alanine aminotransferase (ALT) and creatinine showed a decrease (P<0.05) with the inclusion of DRC. The brightness values (L), yellow-green (a*) and yellow-blue color (b*) of the breast meat did not differ (P>0.05) due to the inclusion of DRC and with the addition or not of carbohydrases, in evaluation 15 minutes post mortem. In the analysis 24 hours post mortem there was significant interaction (P<0.05) between supplementation of carbohydrases and DRC for the variable L. The analyzed values of pH, water holding capacity (WHC) and shear strength (SS) of breast meat were not affected (P>0.05) by inclusion of DRC and addition or not of carbohydrases. The cooking loss (CL) was influenced (P <0.05) by levels of inclusion of DRC. The L* variables and the feet of broiler chickens were not affected (P>0.05) by levels of DRC and addition or not of carbohydrases. The color variable b * showed a decrease (P <0.05) at DRC inclusion level of 5%. The DRC can be used in the diets for broilers from 1 to 21 days old until the assessed level of 10%, associated with the use of carbohydrases, without affecting the performance or carcass yield and poultry cuts at the age of slaughter and meat quality